2018
DOI: 10.3389/fphar.2018.00004
|View full text |Cite
|
Sign up to set email alerts
|

CP-25 Attenuates the Activation of CD4+ T Cells Stimulated with Immunoglobulin D in Human

Abstract: Researchers have shown that the level of immunoglobulin D (IgD) is often elevated in patients with autoimmune diseases. The possible roles of IgD on the function of human T cell activation are still unclear. Paeoniflorin-6′-O-benzene sulfonate (code: CP-25), the chemistry structural modifications of paeoniflorin, was a novel drug of anti-inflammation and immunomodulation. The aims of this study were to determine if human CD4+ T cells could be activated by IgD via the IgD receptor (IgDR)-Lck pathway and whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 40 publications
(53 reference statements)
0
11
0
Order By: Relevance
“…Activated T cells, together with high expression of CD69 and CD154 (CD40L), play vital roles in RA-associated inflammation by producing inflammatory cytokines, which induce synovium inflammation and immune responses (33,34). We previously demonstrated that IgD increases the percentage of CD69 + and CD154 + cells, which might contribute to the elevated IgDR expression and Lck tyrosine phosphorylation (19). The specific blocking of the activated T cells induced by IgD suggests that IgD-Fc-Ig may prevent T cell over-proliferation and activation through selectively targeting IgDR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Activated T cells, together with high expression of CD69 and CD154 (CD40L), play vital roles in RA-associated inflammation by producing inflammatory cytokines, which induce synovium inflammation and immune responses (33,34). We previously demonstrated that IgD increases the percentage of CD69 + and CD154 + cells, which might contribute to the elevated IgDR expression and Lck tyrosine phosphorylation (19). The specific blocking of the activated T cells induced by IgD suggests that IgD-Fc-Ig may prevent T cell over-proliferation and activation through selectively targeting IgDR.…”
Section: Discussionmentioning
confidence: 99%
“…Save for the control group, cells were stimulated with 3 µg/mL of IgD or anti-CD3/CD28 (0.4 µg/mL) in combination with different concentrations of IgD-Fc-Ig fusion protein (1, 3, and 10 µg/mL) for 48 h at 37 • C. A Lck inhibitor A770041 group was used as a positive control, while the IgG 1 -Fc protein treatment group was used as a negative control. After treatment, a Cell Counting Kit-8 (CCK-8) was used to evaluate cell proliferation using stimulation indices according to published protocols (17,19).…”
Section: Human Cell Isolation and Viability Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Binding between IgD and IgDR was clearly concentration-dependent. We have estimated the IgD binding affinity by performing a fluorescence-based receptor binding assay, with high-affinity (KD value was 0.216 nmol/L) [17]. We also identified IgDbinding IgDR as a ∼70 kDa protein complex that was detected on rheumatoid arthritis (RA)-fibroblast-like synoviocytes (FLSs) by using flow cytometry (FCM), confocal laser scanning microscopy and western blot [18].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports also suggested significantly high levels of sIgD, mIgD, and IgDR in RA patients. In human, treatment with IgD could enhance the activation of peripheral blood mononuclear cells (PBMCs) [15], and amplify the activation of CD4 + T cells, which could be mediated by Lck phosphorylation [17]. In Daudi cell line, which is the human Burkitt lymphoma B-cell line, we have investigated that human IgD antibody could induce cell proliferation potentially by activating the putative IgDR to initiate tyrosine phosphorylation signaling cascade that accelerated G1/S transition [19].…”
Section: Introductionmentioning
confidence: 99%